(untitled) (American Journal of Islam and Society, 2019)
Recent work has drawn attention to the state-led and media-driven discourse of "good" and "bad" Muslims. It is a flexible discourse, with benchmarks and shifting appraisals, that aims to mold American Muslims into "good" secular Muslims. Drawing on old Orientalist representations, this American Islamophobic framework strives to produce "good" Blackamerican Muslims through rendering them as invisible, voiceless, or under the control of allies of the U.S. secular power. The three ethnographic vignettes—a masjid fundraiser, two chaplains, and a political collective—demonstrate that Blackamerican Muslims scholars and leaders are not only disrupting this discursive project, but also undermining negative portrayals of Muslims and Islam more broadly. In addition, through their practice and discourse, these Blackamerican Muslim figures are formulating an emergent American Muslim religious identity.